ANALISIS USABILITY PADA APLIKASI ALINGKA MENGGUNAKAN METODE COGNITIVE WALKTHROUGH - Ajeng Fadila Aprilina; Muhamad Azrino Gustalika (JURNAL ILMIAH INFORMATIKA, 2023)
Current developments the mission to achieve innovation through the use of technology. This technology makes interactions between government and citizens more accessible. Technological life forced Baubau City to create ALINGKA software that can help people in emergency situations. The success of your software can be determined by usability testing. Though, this application has not been tested. Usability testing is to find out how far the ALINGKA application can run properly. The goal is to find the results of applying ALINGKA with the cognitive walkthrough method, and provide recommendations for improvement. Respondent data was collected by questionnaire. Respondents in this study were the people of Wolio District, Baubau City who were obtained according to the Taro Yamane formula, then filtered using purposive sampling according to predetermined criteria so that 15 specific respondents were obtained. Obtained by calculating the success rate of 84% which is the average success rate of the respondent's work situation. Respondents spent time working on task scenarios which were calculated using the time to complete the task at a rate of 0.118 goals/second. Calculations from this study show that from a usability point of view the ALINGKA application there are still many application menus that need to be updated.